Auditoría de Gestión al Componente Talento Humano y Administrativo de la Unidad Educativa Fiscomisional San Juan Bautista de Catamayo, Periodo enero-diciembre 2021 - Guajala Gaona, Yaleny Alexandra (2024)
"The Curricular Integration Work Management Audit of the Human Talent and Administrative Component of the Fiscal Commissionary Educational Unit San Juan Bautista de Catamayo, January-December 2021, was carried out with the main objective of evaluating the internal control system. The integration of approaches such as SWOT analysis (FODA in Spanish) and the internal control questionnaire provided a comprehensive perspective of the institutional situation. Likewise, management indicators were applied to measure efficiency and effectiveness in the management of human resources, and the final objective concluded with the presentation of a report addressed to the executives, proposing corrective actions to drive improvements and contribute to the continuous development of the educational institution. To meet the requirements of the Management Audit, research methods were employed to gather the necessary information. Thanks to these methods, it was possible to carry out the five phases of the Management Audit, starting with the work order, cover letter, initial notification, time and task distribution sheets, as well as the scorecard and indices sheet. Upon completing this work and evaluating the internal control system, critical areas for improvement were identified. Among them, the lack of updating of the institutional educational plan and the organizational structure chart stood out, affecting the direction and objectives of the institution. Additionally, a lack of training in the workplace and social security was evident, as well as the absence of evaluations for personnel, making performance monitoring difficult. The hiring of administrative personnel without appointments was also noted, affecting job stability. The lack of management audits makes it difficult to evaluate efficiency, effectiveness, and compliance with activities. Recommendations focus on taking corrective measures to stimulate improvements and favor the constant progress of the educational institution.